Intracellular uptake of EGCG-loaded deformable controlled release liposomes for skin cancer. (2nd April 2020) - Marwah, M.; Perrie, Y.; Badhan, R. K. S.; Lowry, D.
Abstract: Caucasian population groups have a higher propensity to develop skin cancer, and associated clinical interventions often present substantial financial burden on healthcare services. Conventional treatments are often not suitable for all patient groups as a result of poor efficacy and toxicity profiles. The primary objective of this study was to develop a deformable liposomal formulation, the properties of which being dictated by the surfactant Tween 20, for the dermal cellular delivery of epigallocatechin gallatein (EGCG), a compound possessing antineoplastic properties. The results demonstrated a significant ( p  ≤ 0.05) decrease in liposome deformability index (74 ± 8 to 37 ± 7) as Tween 20 loading increased from 0 to 10% w/w, indicating an increase in elasticity. EGCG release over 24-h demonstrated Tween 20 incorporation directly increased release from 13.7% ± 1.1% to 94.4% ± 4.9% (for 0 and 10% w/w Tween 20 respectively). Finally, we demonstrated DilC-loaded deformable liposomes were localized intracellularly within human dermal fibroblast and keratinocyte cells within 2 h. Thus, it was evident that deformable liposomes may aid drug penetration into dermal cells and would be useful in developing a controlled-release formulation.